Core self-evaluations, self-leadership, and the self-serving bias in managerial decision making: A laboratory experiment - Matteo Cristofaro; Pier Luigi Giardino (Administrative Sciences, 2020)
The self-leadership construct has received great attention from scholars over the last 40 years due to its capacity to influence personal effectiveness. However, despite strongly influencing individuals' self-efficacy, performed studies did not determine whether self-leadership is connected, and how, with the Core-Self Evaluation (CSE) trait-a complex personality disposition based on self-efficacy, self-esteem, locus of control, and emotional stability-that has been found impacting decision-making processes within organizations. Moreover, it has not been identified whether individuals with a high level of self-leadership are more prone to be victims of some cognitive biases in decision-making processes, such as the internal attribution of successes and external attribution of failures (i.e., Self-Serving Bias, SSB) that are usually led by the strong belief of individuals in their own capacities. The outlined gaps can be substantiated by the following two research questions: "How is self-leadership related with CSE?" and "How does self-leadership influence the attribution of successes/failures?". To answer these questions, the following were identified and analyzed for 93 executives: (i) the tendency in the attribution of successes and failures, (ii) the CSE, and (iii) their self-leadership level. Results show that: (i) a high level of CSE is connected with high levels of self-leadership; (ii) high levels of self-leadership bring individuals to the internal attribution of successes and external attribution of failures. This work reinforces the stream of (the few) studies that considers a high level of CSE and self-leadership as not always being desirable for managerial decision-making processes and consequent performance. This paper aims to enrich the debate concerning the relations between, on the one hand, self-leadership and, on the other hand, personality traits between self-leadership and decision making.
Keywords: 350; behavioral strategy; biases; cognition; core self-evaluations; decision making; personality; self-leadership; self-serving bias